Limonite – a weathered residual soil heterogeneous at all scales. Issue 3 (28th September 2012) - Airey, D.; Suchowerska, A.; Williams, D.
Abstract : Limonite is a residual soil produced by the decomposition of magnesium silicate (olivine) rocks in tropical environments. During weathering most of the original rock is leached away leaving only its iron content, which is precipitated out in the form of iron sesqui-oxides to create a soft and highly porous soil. The predominant mineral present in limonite is goethite, which forms acicular nanoparticles that agglomerate to produce a silty sand with porous particles. The void ratio varies from 2 to 6, with higher values being a consequence of structure-supported voids. An extensive set of laboratory tests have been performed on a limonite soil profile which extends 50 m to rock. These data show that there is no pattern to shear strength with depth, with the shear strength equally likely to be 50 or 200 kPa through much of the profile. It is argued that the shear strength parameters for failure mechanisms, having any significant length, should be based on average values. The letter presents scanning electron microscopy photographs showing the fundamental particles, the results of triaxial tests comparing natural and reconstituted behaviour which show the effects of microstructure on the meso-scale response, and field data to show site variability.